Imaginative Reconstruction of the Life In Works of William Golding: Exploring the lives of Neanderthals in an eternal present (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This novel is an imaginative reconstruction of the lifeof a band of Neanderthals. It is written in such a way that the reader mightassume the group to be modern Homosapiens as they gesture and speak simply among themselves, and burytheir dead with heartfelt, solemn rituals. They also have powerful senseimpressions and feelings, and appear sometimes to share thoughts in anear-telepathic way. As the novel progresses it becomes more and more apparentthat they live very simply, using their considerable mental abilities toconnect to one another without extensive vocabulary or the kinds of memoriesthat create culture. They have wide knowledge of food sources, mostly roots andvegetables. They chase hyaenas from a larger beast's kill and eat meat, butthey don't kill mammals themselves. They have a spiritual system centring on afemale principle of bringing forth, but their lives are lived so much in thepresent that the reader realizes they are very different from us, living insomething like an eternal present, or at least a present broken and shaped byseasons.